2003
DOI: 10.1111/1475-6773.00134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medicaid Managed Care Programs on Health Services Access and Use

Abstract: Objective. To estimate the effects of Medicaid managed care (MMC) programs on Medicaid enrollees' access to and use of health care services at the national level. Data Sources/Study Setting. 1991-1995 National Health Interview Surveys (NHIS) and a 1998 Urban Institute survey on state Medicaid managed care programs. Study Design. Using multivariate regression models, we estimated the effect of living in a county with an MMC program on several access and use measures for nonelderly women who receive Medicaid thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 12 publications
3
50
1
Order By: Relevance
“…Studies of the effect of MMC on women's health were also mixed. Women's participation in Medicaid HMO programs reduced non-ER use and increased reported unmet need for medical care (Garrett, Davidoff, and Yemane 2003), but had no effect on prenatal care use, birth outcomes, and cesarean section rates (Kaestner, Dubay, and Kenney 2002).…”
Section: Effect Of MMC On Overall Health Care Access and Utilizationmentioning
confidence: 99%
“…Studies of the effect of MMC on women's health were also mixed. Women's participation in Medicaid HMO programs reduced non-ER use and increased reported unmet need for medical care (Garrett, Davidoff, and Yemane 2003), but had no effect on prenatal care use, birth outcomes, and cesarean section rates (Kaestner, Dubay, and Kenney 2002).…”
Section: Effect Of MMC On Overall Health Care Access and Utilizationmentioning
confidence: 99%
“…As such, we developed a proxy measure for managed care enrollment, admittedly a less than ideal measure of actual managed care enrollment information. Building on previous research (Garrett, Davidoff, and Yemane 2003;Zuckerman, Brennan, and Yemane 2002), we based our proxy measure of managed care status on whether the individual lived in a county with a MMC program.…”
Section: Data Sourcesmentioning
confidence: 99%
“…National estimates of the impacts of MMC on other segments of the Medicaid population have been published (Currie and Fahr 2002;Kaestner, Dubay, and Kenney 2002;Garrett, Davidoff, and Yemane 2003;Zuckerman, Brennan, and Yemane 2002). To our knowledge, however, no comparable study has examined the effects of managed care on Medicaid beneficiaries with disabilities.…”
mentioning
confidence: 99%
“…However, research has shown that PCCM increased the chances of a beneficiary seeing a physician relative to traditional Medicaid in the late 1980s (Hurley, Freund, and Paul 1993). More recent evidence on PCCMs in the context of a health care market that is more dominated by other forms of managed care suggest that Medicaid PCCMs have little effect on the likelihood that a beneficiary sees a physician (Garrett, Davidoff, and Yemane 2001).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…When this is the case, beneficiaries are required to select one of the two programs when they enroll. For those who do not choose, it is most common for them to be assigned to a PCCM provider (Garrett, Davidoff, and Yemane 2001). However, in some states, beneficiaries are assigned to PCCM or an HMO either randomly or based on place of residence.…”
Section: Conceptual Frameworkmentioning
confidence: 99%